2016
DOI: 10.1039/c5cy01866h
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic dehydration of ethanol over hierarchical ZSM-5 zeolites: studies of their acidity and porosity properties

Abstract: The catalytic activity of novel micro/mesoporous ZSM-5 in the dehydration process of alcohols has been studied with respect to their acidity and porosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 73 publications
0
39
0
2
Order By: Relevance
“…S7 †). [41][42][43] The TIPB conversion data of both parent and modied zeolites are presented in Table 4 (the product selectivity values are available in Table S2 †). It has been shown that the activity of zeolite based catalysts in this reaction is determined by the accessibility of BAS to the bulky TIPB molecules.…”
Section: Resultsmentioning
confidence: 99%
“…S7 †). [41][42][43] The TIPB conversion data of both parent and modied zeolites are presented in Table 4 (the product selectivity values are available in Table S2 †). It has been shown that the activity of zeolite based catalysts in this reaction is determined by the accessibility of BAS to the bulky TIPB molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Other dehydration catalysts, namely H‐ZSM‐5–25, γ‐Al 2 O 3 , ZnO, and MgO, were tested as well. These catalysts were chosen because of their acid–base properties ranging from acidic to amphoteric to basic and their well‐known ability for dehydration of alcohols . Over such catalysts, water can be eliminated by E 1 ‐, E 2 ‐, or E 1cb ‐like mechanisms, depending on catalyst properties and the structure of the reactant .…”
Section: Resultsmentioning
confidence: 99%
“…These catalysts were chosen because of their acid-base properties ranging from acidic to amphoteric to basic and their well-knowna bility for dehydration of alcohols. [43][44][45] Over such catalysts, water can be eliminated by E 1 -, E 2 -, or E 1cb -like mechanisms, [46] depending on catalystp roperties and the structure of the reactant. [47] However,w ith LCM as reactant, none of the catalysts was ablet of acilitated ehydration to acrylamide or ACN.…”
Section: Catalytic Dehydrationofl Actamidementioning
confidence: 99%
“…Among them, the most undesired path is the ethanol conversion to ethylene as the latter is easily transformed into the carbonaceous deposit. The ethanol dehydration to ethylene is undergone in the presence of acid sites (Tarach et al, 2016;Gołąbek et al, 2018). Therefore, the relative share of individual side reactions strongly depends on the acid/redox characteristic of the catalyst, but also on the applied reaction variables (e.g., temperature, EtOH/H 2 O ratio, and contact time).…”
Section: Introductionmentioning
confidence: 99%